Eltern, Schule, Aushandlung: Chancen und Grenzen demokratischer Schulentwicklung im Kontext von Vielfalt - Werthern, Katjuscha von (International Dialogues on Education Journal, 2017)
In educational policy and practical school discourse, cooperation between parents and schools is generally considered important in promoting more equal-opportunity education, but is also described as difficult in terms of implementation. The relationship between schools and parents with a so-called migration background (Migrationshintergrund) is the subject of a great deal of discussion, and these parents are frequently assigned responsibility of a lack in cooperation. In this contribution, I will show that the classification of an entire group of parents as bildungsfern (literally “far from education”) is part of the problem. (This problematic term is currently used in Germany to designate those population groups that in Anglo-American discourse are labelled “educationally disadvantaged”.) Classical forms of participation such as parents’ associations are insufficient and do not live up to parental diversity. The concept of democratic school-development (Schütze & Hildebrandt 2006) tries to engage all the parents in a school to minimize exclusion and institutional hierarchies. The starting point of this study, presented here in sections, is whether this can succeed over the long term. Democratic processes of school development offer great potential to approach diversity constructively and to make schools more democratic. But such processes, it seems, can never be considered completed, but need to be seen as an ongoing development in which all participants need to be involved in ever new ways and where the aims require constant renegotiation.